1997
DOI: 10.1038/sj.ejcn.1600425
|View full text |Cite
|
Sign up to set email alerts
|

Validation of dietary intakes of protein and energy against 24 hour urinary N and DLW energy expenditure in middle-aged women, retired men and post-obese subjects: comparisons with validation against presumed energy requirements

Abstract: Objectives: To compare validation of reported dietary intakes from weighed records against urinary nitrogen excretion and energy expenditure measured by DLW, and to examine the utility of the Goldberg cut-off for EI:BMR in the identi®cation of under-reporters. Design: Energy (EI) and nitrogen (protein) intake (NI) were measured by 16 d of weighed diet records collected over 1 y. They were validated against urinary nitrogen excretion in 5±8 (mean 6.0) 24 h urine collections and total energy expenditure (EE) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 16 publications
7
76
0
6
Order By: Relevance
“…Although good agreement between measured metabolizable intake and observed energy intake calculated from dietary intake assessment methods has been demonstrated (Davies et al, 1994), several other studies have reported underestimations of habitual intake Livingstone et al, 1990Livingstone et al, , 1992Schoeller et al, 1990;Black et al, 1997). Work by Davies et al (1994) and the present study indicate a moderate but not signi®cant bias of weighed food records against doubly labelled water in infants and young children.…”
Section: Discussionsupporting
confidence: 62%
“…Although good agreement between measured metabolizable intake and observed energy intake calculated from dietary intake assessment methods has been demonstrated (Davies et al, 1994), several other studies have reported underestimations of habitual intake Livingstone et al, 1990Livingstone et al, , 1992Schoeller et al, 1990;Black et al, 1997). Work by Davies et al (1994) and the present study indicate a moderate but not signi®cant bias of weighed food records against doubly labelled water in infants and young children.…”
Section: Discussionsupporting
confidence: 62%
“…The present study found a correlation of 0⋅68 between urinary N and DLW EE, but excluding two extreme values reduced the correlation to 0⋅32 (NS). In a larger body of data (including the present data) (Black et al 1997), the correlation between urinary N excretion and DLW EE was 0⋅36 (n 45) (P Ͻ 0⋅05), but that between urinary N excretion and protein intake was 0⋅80 (excluding under-reporters). Thus, these methods are not completely interchangeable.…”
Section: Comparison Of Validation Techniquesmentioning
confidence: 41%
“…The criterion for under-reporting (EI : EE Ͻ 0⋅79) tends to identify a higher proportion of under-reporters than the criterion urinary N : NI Ͼ1⋅0. It is uncertain whether this is due to inherent differences in the criteria or to genuine differences in the reporting of protein and energy (Black et al 1997). As an alternative to measured EE, EI : BMR has limitations as a validator.…”
Section: Comparison Of Validation Techniquesmentioning
confidence: 99%
“…The methods used to determine energy misreporting in children and adolescents have been described in detail previously [22]. Briefly, energy misreporting was assessed using Goldberg's cut-off2 criterion [23,24], which uses 95% confidence limits to statistically compare the ratio of reported energy intake (EI) to basal metabolic rate (BMR) with physical activity level (PAL). PAL was adapted to children and corresponded to light physical activity (1.45-1.60 depending on age and gender) [22].…”
Section: Assessment Of Under-reportingmentioning
confidence: 99%